Geochemical characteristics and genesis of the Ordovician sub-salt natural gas in the Ordos Basin, China - Shi, Jianglong; Guo, Ying; Li, Jian; Du, Guanghong; Jing, Xianghui; Liu, Gang; Huang, Junping; Fang, Chenchen; Zhang, Tingting (Frontiers in Earth Science, 2023)
With the further exploration of deep natural gas, a mass of natural gas resources have been found in the Ordovician subsalt strata, while the genetic types and sources of subsalt natural gas are still in controversy. Based on the components, carbon and hydrogen isotopic ratios of natural gas from the latest exploration wells, combined with the geological background, this study systematically analyzed the genetic types and sources of subsalt natural gas of the central and eastern Ordos Basin. The results show that the Ordovician natural gas was mainly composed of hydrocarbon gases with low content of heavy hydrocarbons and dryness (CCH4/CCH4+) above 0.95, belonging to typical dry gas. Non-hydrocarbon gases mainly includ N2 and CO2, and some natural gas samples contained H2S. The Ordovician subsalt natural gas was primarily a self-generating and self-preserving oil-cracking gas with relatively high maturity (Ro ranging from 1.5% to 2.1%) mixed with coal-derived gas generated by upper-Paleozoic coal with relatively low maturity (Ro ranging from 1.1% to 1.5%). The carbon isotope ratio of alkane gas in the Ordovician subsalt shows considerably high, and mainly exhibited δ 13 C1<δ 13 C2<δ 13 C3<δ 13 C4 (a positive carbon isotope sequence), while some samples exhibited the isotope reversal (δ 13 C1<δ 13 C2>δ 13 C3 and δ 13 C1>δ 13 C2<δ 13 C3), which was mainly influenced by thermochemical sulfate reduction (TSR) and 2 / 19 the mixing of gases with different maturities or source rocks.